Development Of Creativity of Future Teachers - Ablakulov Sherali Davronovich (Genius Journals, 2022)
The article discusses the features of the development of creativity of future teachers. The psychological and pedagogical conditions for the formation of students' creative potential are characterized. The heuristic methods of organizing classes are analyzed and the expediency of their application in the process of professional training of future teachers is substantiated
Keywords: Creativity of future teachers; heuristic teaching methods; professional training, creativity; creative thinking